A Challenges in Implementing Package of Essential Noncommunicable Diseases Interventions in Iran's Healthcare System - Koorosh Etemad; Alireza Heidari; MohammadHossein Panahi; Mansureh Lotfi; Fatemeh Fallah; Sadaf Sadeghi (Mazandaran University of Medical Sciences, 2016)
Introduction and purpose: The World Health Organizatoin Package of Essential Noncommunicable (PEN) Diseases Interventions is a prioritized set of costeffective interventions that can provide quality care even in the low-resource settings. The present study aimed to determine the challenges of implementing this package in Iran’s healthcare system. Methods: This qualitative study was conducted using the content analysis approach in 2015. The data were collected by holding two focus group discussions and six depth interviews with the participation of 18 experts. Following the transcription of the interviews, the data were analyzed tthrough the content analysis method. Results: The findings were categorized into nine main themes, including: management challenges, organizational challenges, functional challenges, intelligence challenges, political challenges, demographic challenges, economic challenges, cultural challenges, and educational challenges, out of which 19 subthemes were derived. Conclusion: Effective and sustained management, health system restructuring, cooperation of other sectors, and training can aid with overcoming the multitude of obstacles and accelerating the implementation of the PEN.